The role of the public sector in the policy of social integration: An example of the municipality of Malmö (Revista LIDER, 2020)
The objective of this article is to discuss the new challenges of the welfare state in a multicultural society and the role of the public sector and it´s key institutions such as schools, social services and the healthcare sector in the integration process. Central to this discussion are the characteristics that create social capital. I exemplify this discussion with the presentation of the project regarding social promoters, which I associate with the role of the public sector and local government officials.